2003
DOI: 10.1164/rccm.200207-752oc
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancies between Perceptions by Physicians and Nursing Staff of Intensive Care Unit End-of-Life Decisions

Abstract: Several studies have pointed out ethical shortcomings in the decision-making process for withholding or withdrawing life-supporting treatments. We conducted a study to evaluate the perceptions of all caregivers involved in this process in the intensive care unit. A closed-ended questionnaire was completed by 3,156 nursing staff members and 521 physicians from 133 French intensive care units (participation rate, 42%). Decision-making processes were perceived as satisfactory by 73% of physicians and by only 33% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
161
6
17

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 258 publications
(196 citation statements)
references
References 30 publications
12
161
6
17
Order By: Relevance
“…Decisions regarding the patient's treatment and therapies are the responsibility of the physicians [37]. Nursing staff hardly ever formally participate in the decision-making process regarding the therapeutic methods used, even though patient care and nursing are among the key tasks of nursing staff [50]. The current study confirms that misunderstandings and doubts concerning therapeutic measures taken are still significant stressors for nurses.…”
Section: Discussionsupporting
confidence: 60%
“…Decisions regarding the patient's treatment and therapies are the responsibility of the physicians [37]. Nursing staff hardly ever formally participate in the decision-making process regarding the therapeutic methods used, even though patient care and nursing are among the key tasks of nursing staff [50]. The current study confirms that misunderstandings and doubts concerning therapeutic measures taken are still significant stressors for nurses.…”
Section: Discussionsupporting
confidence: 60%
“…And the differences were quite large. Thomas et al 33 reported that 73% of physicians but only 33% of nurses in their study thought that their relationships were collaborative; Ferrand et al 19 found that 50% of the physicians but only 27% of the nurses identified relationships with physicians as collaborative. Studies also reported that nurses' perceptions of the degree and quality of collaboration were a more accurate predictor of patient outcomes-deaths and transfer back to the ICU-than were physicians' perceptions.…”
Section: Types and Measurement Of Nurse-physician Relationshipsmentioning
confidence: 97%
“…[18][19][20][21] In all of these writings, what constitutes good or high-quality relationships between physicians and nurses is seldom defined, and when an attempt is made to assess goodness, nurse-physician relationships are measured as though all interactions between nurses and physicians on …”
mentioning
confidence: 99%
“…Nonetheless, there is ample evidence that there remains significant room for improvement in the care of these patients. (6,7,8,9) Due to inherent challenges in assessing patients' dying experience, it is difficult to measure the quality of care of these patients. Surrogate markers such as ICU length of stay are markers of intensity of care, but may not directly reflect the quality of endof-life care.…”
Section: Introductionmentioning
confidence: 99%